Evaluasi Sifat Mekanis Beton Menggunakan Agregat Kasar Batu Andesit Toraja Utara - Israel Padang; Hernita Matana; Yulius Pakiding; Fiki Kogoya; Zet Karangan (Jurnal Karajata Engineering, 2026)
The increasing demand for concrete has intensified the exploitation of natural coarse aggregates, while large quantities of andesite waste generated from stone-carving activities in North Toraja remain underutilized. This study investigates the feasibility of using locally sourced andesite waste as a 100% replacement for conventional coarse aggregate in normal-strength concrete. Concrete specimens with a target compressive strength of 20 MPa were prepared and tested for workability, compressive strength at 3, 7, 14, and 28 days, and splitting tensile strength at 28 days. Experimental results showed that the andesite aggregate satisfied all standard requirements for coarse aggregates. The concrete containing andesite aggregate achieved a 28-day compressive strength of 18.02 MPa and a splitting tensile strength of 2.93 MPa, compared with 19.82 MPa and 3.16 MPa for the control concrete, representing reductions of approximately 9.1% and 7.3%, respectively. Despite these reductions, the concrete remained within the range of normal-strength structural concrete. The findings demonstrate that waste andesite from local stone-processing activities can be utilized as an alternative coarse aggregate, contributing to sustainable construction practices and reducing dependence on natural aggregate resources.